(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Biosurfactant are amphiphilic biomolecules, with hydrophobic and hydrophilic portions, the hydrophobic part of the molecule is based on saturated or unsaturated fatty acids, the hydrophilic portion can be either cationic and anionic amino acids or mono-and di-saccharides (rhamnose and trehalose respectively).To present study totally seven sampling stations were selected from Tirunelveli and its surrounding area in order to isolate biosurfactant producing organisms.Other more elaborate techniques including chromatography-mass spectroscopy (GC-MS). In the Gas Chromatography-Mass Spectroscopy (GC-MS) analysis, biosurfactant produced by Pseudomonas aeruginosa strain S1RU2 showed various compounds. The compounds such as, “Hexadecenoic acid, Z-11-”, “9-Octadecenoic acid, (E)-”, “Cyclotetradecane”, “1,2-Benzenediol, 3,5-bis(1,1-dimethylethyl)-”,“2-Ethylacridine”,“Pyrido[2,3-d]pyrimidine,4- phenyl”,“Octasiloxane,1,1,3,3,5,5,7,7,9,9,11,11,13,13,15,15-hexadecamethyl-”,“5-Methyl-2- trimethylsilyloxy-acetophenone”, “5-Methyl-2-phenylindolizine”, “n-Propyl 11-octadecenoate”, “2,4-Cyclohexadien-1-one,3,5-bis(1,1-dimethylethyl)-4-hydroxy-”,“2-Ethylacridine”, “Cyclobarbital”, “Benzo[h]quinoline, 2,4-dimethyl-” were identified using Gas chromatography-mass spectroscopy (GC-MS) analysis.Together with the GC-MS research proves that the biosurfactant is a glycolipid.